The Influence Of Farmers, Middlemen, Social And Economic Factors On The Agricultural Sector In Adiankoting Sub-District - Rut Anatasya Simatupang; Annisa Ilmi Faried; Rahmad Sembiring (Universitas Dehasen Bengkulu, 2026)
The agricultural sector is the main foundation of livelihood for the community in Adiankoting District, where the majority of residents depend on farming activities. However, efforts to improve agricultural productivity face various challenges related to social and economic factors, as well as the unequal relationship between farmers and middlemen.Farmers often experience limitations in capital, technology, and market access, which force them to rely on middlemen who frequently offer low selling prices and place farmers in a disadvantaged position. Economically, the agricultural sector in Adiankoting is also affected by price fluctuations, dependence on unpredictable seasons, and the lack of supporting facilities such as irrigation and access to agricultural credit.Despite these challenges, agriculture remains the backbone of the local economy, influencing farmers’ income, household welfare, and overall village development. With a land area of 502.90 km² and comprising 16 villages, Adiankoting District holds significant agricultural potential, particularly in larger areas such as Dolok Nauli Village. Understanding the influence of social and economic factors, as well as the roles of farmers and middlemen, is essential for identifying appropriate solutions to improve farmers’ welfare and promote sustainable agricultural development in Adiankoting District.